Dietary broccoli impacts microbial community structure and attenuates chemically induced colitis in mice in an Ah receptor dependent manner. (October 2017) - Hubbard, Troy D.; Murray, Iain A.; Nichols, Robert G.; Cassel, Kaitlyn; Podolsky, Michael; Kuzu, Guray; Tian, Yuan; Smith, Phillip; Kennett, Mary J.; Patterson, Andrew D.; Perdew, Gary H.
Highlights: Dietary broccoli activates the colonic AHR the high ligand affinity AHR b in mice. Dietary broccoli influences the composition of the mouse cecal microbiome. Dietary broccoli decreases inflammation in the gastrointestinal tract of AHR b mice. Dietary broccoli protects the GI tract of AHR b, but not AHR d mice from toxic insult. Abstract: Consumption of broccoli mediates numerous chemo-protective benefits through the intake of phytochemicals, some of which modulate aryl hydrocarbon receptor (AHR) activity. Whether AHR activation is a critical aspect of the therapeutic potential of dietary broccoli is not known. Here we administered isocaloric diets, with or without supplementation of whole broccoli (15% w/w), to congenic mice expressing the high-affinity Ahr b/b or low-affinity Ahr d/d alleles, for 24 days and examined the effects on AHR activity, intestinal microbial community structure, inflammatory status, and response to chemically induced colitis. Cecal microbial community structure and metabolic potential were segregated according to host dietary and AHR status. Dietary broccoli associated with heightened intestinal AHR activity, decreased microbial abundance of the family Erysipelotrichaceae, and attenuation of colitis. In summary, broccoli consumption elicited an enhanced response in ligand-sensitive Ahr b/b mice, demonstrating that in part the beneficial aspects of dietary broccoli upon intestinal health are associated with heightened AHR activity.